2021
DOI: 10.2147/ijn.s290466
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, Pharmacokinetic, and Therapeutic Potential of Novel 6-Mercaptopurine-Loaded Oral Nanomedicines for Acute Lymphoblastic Leukemia

Abstract: Background Acute lymphoblastic leukemia (ALL) is the most common hematologic malignancy in children. It requires a long and rigorous course of chemotherapy treatments. 6-Mercaptopurine (6-MP) is one of the primary drugs used in chemotherapy. Unfortunately, its efficacy has been limited due to its insolubility, poor bioavailability and serious adverse effects. To overcome these drawbacks, we constructed 6-mercaptopurine (6-MP)-loaded nanomedicines (6-MPNs) with biodegradable poly(lactide-co-glycoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…Such results are consistent with previous reports, and no researcher has reported antiproliferative nor apoptotic effect at concentrations lower than 1 µM [12,22]. In addition, 6-MP is metabolized into their active metabolites also called tioguanine nucleotides (TGN), which are also substrates of MRP4 [23] leading to an even lower concentration of active metabolites than 0.1 µM. Any 6-MP concentration once inside the cell will be decreased by MRP4 activity.…”
Section: Discussionsupporting
confidence: 92%
“…Such results are consistent with previous reports, and no researcher has reported antiproliferative nor apoptotic effect at concentrations lower than 1 µM [12,22]. In addition, 6-MP is metabolized into their active metabolites also called tioguanine nucleotides (TGN), which are also substrates of MRP4 [23] leading to an even lower concentration of active metabolites than 0.1 µM. Any 6-MP concentration once inside the cell will be decreased by MRP4 activity.…”
Section: Discussionsupporting
confidence: 92%
“…We further confirmed that 6-MPNs were able to improve the peak concentration (C max ) and the area under the curve (AUC) of 6-MP in SD rats. 6 The C max (128.10 ng/mL) and AUC (147.3 ± 42.89 μg/L•h) of 6-MP in the 6-MPNs group were significantly higher than the C max (44.03 ng/mL) and AUC (70.31 ± 18.24 μg/L•h) of 6-MP in the 6-MPCs group (Figure 1C). There was little difference in the half-life (t1/2) of 6-MP between the 6-MPNs and 6-MPCs groups (1.25 ± 0.33 h and 1.27 ± 0.39 h, respectively).…”
Section: Pharmacokinetic Studiesmentioning
confidence: 90%
“…Preparation of 6-MPNs and 6-MP Suspensions 6-MPNs were prepared by a modified double-emulsion solvent evaporation method. 6 Briefly, 6-MP and poly(vinyl alcohol) (PVA) were dissolved in ammonia water to form the aqueous phase. The drug-containing solution was added dropwise into the ethyl acetate containing PLGA while stirring to achieve w/o emulsion.…”
Section: Preparation and Characteristics Of 6-mpnsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, experts have used magnetic materials such as metal vectors, mesoporous silica, and iron oxide to produce 6 MP nanoparticles. Some researchers have modified these nanoparticles with hyaluronic acid and folic acid to enhance the ability of nanomedicine to target tumors and cells [ 38 ].…”
Section: Introductionmentioning
confidence: 99%